Experiências de crianças santarenas com o rio Tapajós por meio da recreação baseada na natureza - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Nature captivates humans. The nature described here encompasses its biophysical elements, such as fauna, flora, all geological forms, and human presence. Studies on the human-nature relationship report some kind of "affiliation" with nature—an emotional bond with living beings and the natural environment, especially in children, who are naturally curious. Contact with nature can nurture this affiliation through outdoor recreational activities, also known as nature-based recreation (NBR). The types of outdoor environments children use, as well as the categories of natural elements they have access to, are connected to the recreational activities these children engage in. Paradoxically, studies report a decrease in children's experiences with nature due to factors stemming from urbanization, such as reduced green spaces for outdoor activities and the prevalence of electronic media. Various types of NBR enhance both cognitive and emotional development in children. Opportunities for children’s interactions with nature across different environments have been studied in the literature, including environments such as rivers, streams, lakes, and igarapés. This research aimed to understand how children from an urban area (Vista Alegre do Juá), located on the banks of the Tapajos River in Santarém, Pará, experienced contact with the river from an NBR perspective. The study involved 15 children aged 8 to 12 years, regardless of gender, residing in the study area. The methodology included data collection tools such as person-centered behavioral mapping and place-centered behavioral mapping, based on the studies of Sommer and Sommer (2002), Fernandes (2006), Pinheiro et al. (2008), Klein et al. (2018), Santos (2023), and Santos and Novais (2024), utilizing naturalistic observation techniques and the assistance of a field diary. Data generated included percentages, means, and standard deviations (descriptive statistics), as well as tables and graphs for better visualization of the results. Path maps (sectors) were generated using QGIS software version 3.32.0 to understand the occupation of these sectors by the children. The resulting analysis categories were: the main activity performed by the child, types of NBR, sectors of the location traversed, and nature elements used. In this context, activities such as swimming in the river and building sandcastles/digging holes were the most performed by the children, highlighting sectors like the river and its bank. Four types of NBR were categorized (aquatic, terrestrial, associative, and contemplative), with the highest rates for aquatic and associative activities. The nature elements most used by the children were water, sand, and branches/sticks, although objects found on the beach, such as disposable cups, plastic bags, and PET bottles, were also used during recreational activities. Even in an urban context, children perceive nature as a place to be explored for its diversity and for allowing a wide variety of play forms. The blue space landscape, represented by the Tapajos River, provides stimuli to the children’s senses in their affective, cognitive, behavioral, physical, and social aspects. Therefore, promoting the environmental conservation of these environments in urban areas is a crucial step in the planning of public policies, to generate recreation opportunities for today’s children and future generations.
Keywords: Crianças; Recreação baseada na natureza; Espaços azuis urbanos; CNPQ::CIÊNCIAS SOCIAIS APLICADAS; Biodiversidade, saúde e sustentabilidade